Expression of phosphoenolpyruvate carboxykinase linked to chemoradiation susceptibility of human colon cancer cells - Park, Ji-Won (BioMed Central, 2014)
BACKGROUND: Resistance to 5-fluorouracil (5-FU) in patients with colorectal cancer prevents effective treatment and leads to unnecessary and burdensome chemotherapy. Therefore, prediction of 5-FU resistance is imperative. METHODS: To identify the proteins linked to 5-FU resistance, two-dimensional gel electrophoresis-based proteomics was performed using the human colon cancer cell line SNU-C4R with induced 5-FU resistance. Proteins showing altered expression in SNU-C4R were identified by matrix-associated laser desorption/ionization–time-of-flight analysis, and their roles in susceptibility to 5-FU or radiation were evaluated in various cell lines by transfection of specific siRNA or creation of overexpression constructs. Changes in cellular signaling and expression of mitochondrial apoptotic factors were investigated by Western Blot analysis. A mitochondrial membrane potential probe (JC-1 dye) and a flow cytometry system were employed to determine the mitochondrial membrane potential. Finally, protein levels were determined by Western Blot analysis in tissues from 122 patients with rectal cancer to clarify whether each identified protein is a useful predictor of a chemoradiation response. RESULTS: We identified mitochondrial phosphoenolpyruvate carboxykinase (mPEPCK) as a candidate predictor of 5-FU resistance. PEPCK was downregulated in SNU-C4R compared with its parent cell line SNU-C4. Overexpression of mPEPCK did not significantly alter the susceptibility to either 5-FU or radiation. Suppression of mPEPCK led to a decrease in both the cellular level of phosphoenolpyruvate and the susceptibility to 5-FU and radiation. Furthermore, the cellular levels of phosphoenolpyruvate (an end product of PEPCK and a substrate of pyruvate kinase), phosphorylated AKT, and phosphorylated 4EBP1 were decreased significantly secondary to the mPEPCK suppression in SNU-C4. However, mPEPCK siRNA transfection induced changes in neither the mitochondrial membrane potential nor the expression levels of mitochondrial apoptotic factors such as Bax, Bcl-2, and Bad. Downregulation of total PEPCK was observed in tissues from patients with rectal cancer who displayed poor responses to preoperative 5-FU-based radiation therapy. CONCLUSION: Our overall results demonstrate that mPEPCK is a useful predictor of a response to chemoradiotherapy in patients with rectal cancer.